El domador de tornados - Fields, Terri, 1948-; Jacques, Laura (Mt. Pleasant, SC : Arbordale Publishing, 2016)
In this story based on The Emperor's new clothes, when Mayor Peacock commissions Travis the Tornado Tamer to protect the town, the weasel builds a transparent cover that he claims only smart and special people can see. Includes activities.
Includes bibliographical references.
Keywords: Tricksters -- Juvenile fiction; Tornadoes -- Juvenile fiction; Mayors -- Juvenile fiction; Animals -- Juvenile fiction; Spanish language materials; Prestidigitadores -- Novela juvenil; Tornados -- Novela juvenil; Animales -- Novela juvenil